Representasi Dampak Krisis Lingkungan dalam Puisi-Puisi Karya Taufiq Ismail: Kajian Ekokritik Greg Garrard - Nurul Hidayah (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Environmental damage caused by human activities has become an increasingly pressing global issue. Poetry as a literary work has the power to represent ecological problems symbolically and critically. This study aims to describe the representation of the impact of the environmental crisis in Taufiq Ismail's poems, namely